2020
DOI: 10.3389/fimmu.2020.513383
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Early Protein BFRF1 Suppresses IFN-β Activity by Inhibiting the Activation of IRF3

Abstract: Epstein-Barr virus (EBV) is the causative agent of infectious mononucleosis that is closely associated with several human malignant diseases, while type I interferon (IFN-I) plays an important role against EBV infection. As we all know, EBV can encode some proteins to inhibit the production of IFN-I, but it’s not clear whether other proteins also take part in this progress. EBV early lytic protein BFRF1 is shown to be involved in viral maturation, however, whether BFRF1 participates in the host innate immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 117 publications
1
30
0
Order By: Relevance
“…Epidermal ephA2 expression is upregulated in keratinocytes by several pro-inflammatory cytokines, growth factors, and ultraviolet radiation ( 45 ). Hypoxia upregulates both molecules in the skin and lung ( 29 , 46 ). In endothelial cells, proinflammatory cytokines including TNF-α and IL-1β induced the expression of ephrinA1/ephA2 ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidermal ephA2 expression is upregulated in keratinocytes by several pro-inflammatory cytokines, growth factors, and ultraviolet radiation ( 45 ). Hypoxia upregulates both molecules in the skin and lung ( 29 , 46 ). In endothelial cells, proinflammatory cytokines including TNF-α and IL-1β induced the expression of ephrinA1/ephA2 ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of ephA2 significantly reduced KSHV entry and EphA2 overexpression significantly increased EBV infection ( 26 28 ). An EBV-encoded early lytic protein, BERF1, inhibited the IFN-β production, disrupting the host innate immunity ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…HCMV pUL50 and pUL53, like their respective herpesviral homologs, are the core NEC components and major egress regulators. Although the main functions, structural features, and binding properties of these core NEC proteins have been well recognized, several accessory activities have been reported, in particular for the pUL50 groove protein homologs [50][51][52][53][54][55]. In the present study, we focused on directly NEC-dependent and partly NEC-independent functional aspects of HCMV pUL50 through the characterization of the HCMV ∆UL50 deletion mutant.…”
Section: Discussionmentioning
confidence: 99%
“…We also identified STING The regulatory mechanisms by which EBV escapes the innate immune response triggered by primary infection, and the reactivation molecules, have been well characterized. 22,43 KSHV-ORF52 and EBV BLRF2 homologs directly interact with cGAS to control its enzymatic activity. 44 More recently, it was found that EBV BGLF2 binds to STING and suppresses type I IFN production.…”
Section: Discussionmentioning
confidence: 99%